Socio-Demographic Determinants of Genitourinary Prolapse (Journal of Preventive and Social Medicine, 2022)
Background: Genitourinary prolapse is a common gynecological problem, especially in developing country. Causes and risk factors for uterine prolapse are complex and deeply embedded in the cultural, economic and social conditions of women. Prevalence of depression is higher among women with advanced stages of prolapse. Hence this study aimed to assess the socio-demographic factors among patients with genitourinary prolapse.Methods: A cross-sectional study was conducted from January to December, 2013 among 120 women with genital prolapse who attended at Gynae wards of Dhaka Medical College Hospital, Shaheed Suhrawardy Medical College Hospital, and Mitford Hospital in Dhaka. Women who were admitted with complaints of protruding mass per vagina and diagnosed as case of uterine prolapse were assessed and staged accordingly. A semi-structured questionnaire was used to obtain socio-demographic data and prolapse related data by face to face interview. After collection, data were compiled, summarized, and analyzed using SPSS software.Results: In this study, out of 120 genitourinary prolapsed patients, 31.7% were 40-45 years age group, majority of 79.2 % were illiterate and almost two third had no monthly income. Among all respondents, 64.2 % had more than four children, maximum 96.7% had history of home delivery, and 91.7% history of heavy work during pregnancy or just after delivery.Conclusion: Genitourinary prolapsed patients were illiterate, multipara, economic insolvency, heavy work during pregnancy and home delivery. A holistic management approach is recommended for women having prolapse.JOPSOM 2021; 40(2):26-31